A paracrine role for white thermogenic adipocytes in innervation: an evidence-based hypothesis - Lee, Aejin (Neural Regen Res, 2019)
White adipose tissue (WAT) stores energy and also plays an important endocrine role in producing adipokines for communication with the peripheral and central nervous system. WAT consists of the major lipogenic unilocular adipocytes and the minor populations of beige and brite multilocular adipocytes. These multilocular adipocytes express thermogenic genes and have phenotypic similarity with thermogenic brown adipose tissue. According to a current paradigm, multilocular adipocytes have a thermogenic function in WAT. In this mini review, we discuss data revealing heterogeneity among multilocular cell subsets in WAT and their functions beyond thermogenesis. We propose a hypothetical neuroendocrine role for multilocular adipocytes subsets in the formation of adaptive sensory-sympathetic circuits between the central nervous system and adipose tissue, which activate lipolysis and thermogenesis in WAT in high energy demand situations.